2015
DOI: 10.1016/j.enbuild.2015.01.041
|View full text |Cite
|
Sign up to set email alerts
|

Air source heat pump water heaters in residential buildings in Australia: Identification of key performance parameters

Abstract: a b s t r a c tHeat pump water heaters have been increasingly used to promote energy savings in residential buildings. Nonetheless, their performance may vary significantly due to different site-specific characteristics and technical specifications. To examine this issue, this research study sought to identify key performance parameters for air source heat pump water heaters (ASHPWH) in residential buildings in Australia by using a sensitivity analysis through theoretical models calibrated with empirical measu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
28
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(28 citation statements)
references
References 38 publications
(48 reference statements)
0
28
0
Order By: Relevance
“…The investigated retrofitted system has the potential to be more cost-effective if manufactured at larger volumes. In order to reach large production volumes, the retrofitted system needs to successfully get a market share in competition with other solutions for domestic hot water energy saving such as small air-to-water heat pumps which have recently entered into this specific market [44,45].…”
Section: Discussionmentioning
confidence: 99%
“…The investigated retrofitted system has the potential to be more cost-effective if manufactured at larger volumes. In order to reach large production volumes, the retrofitted system needs to successfully get a market share in competition with other solutions for domestic hot water energy saving such as small air-to-water heat pumps which have recently entered into this specific market [44,45].…”
Section: Discussionmentioning
confidence: 99%
“…MA et al (2014) proposed to use solar energy heat pump systems in farms, however, exploiting either heating or cooling individually. Moreover, some heat pump systems have been studied for home application; yet few studies have reported results in farming areas by using distinct sources of energy (STAFFORD & LILLEY, 2012;LUO et al, 2015;VIEIRA et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…It is estimated that the housing sector, regardless of the location of a country on the world map, is responsible for the use of 19 do 50 % of total energy that is required for the existence of households [1]. The use of energy needed for production of domestic hot water forms a considerable proportion in the overall energy balance; it is equal to 18 % in the USA [2], 20% in Brazil [3], 25% in the UK [4], 26% in Spain [5] and 30% in Australia [6].…”
Section: Introductionmentioning
confidence: 99%